Correlation of Blood Lipid and Serum Inflammatory Factor Levels With Hypertensive Disorder Complicating Pregnancy - Chen, Wangxiang; Guo, Yan; Yao, Xia; Zhao, Di (Frontiers in Surgery, 2022)
Purpose: To explore the changes of blood lipid and serum inflammatory factors in pregnant women with hypertensive disorder complicating pregnancy (HDP) and the relationship with disease development. Methods: 107 pregnant women with HDP who had regular prenatal examination in our hospital from July 2018 to July 2021 were selected as the research objects. According to the severity of the disease, they were divided into gestational hypertension group, mild preeclampsia group and severe preeclampsia group. 30 healthy pregnant women who underwent prenatal examination in the same period were selected as the healthy group. Serum total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), lipoprotein-associated phospholipaseA2 (Lp-PLA2), C- reactive protein (CRP), interleukin -6(IL-6), tumor necrosis factor-α (TNF-α) were measured. ROC was used to analyze the predictive value of blood lipid and serum inflammatory factors in pregnant women with HDP. Results: The levels of serum TC, TG and LDL-C increased with the progression of HDP, the level of serum HDL-C decreased with the progression of HDP (P<0.05). The levels of serum Lp-PLA2, CRP, IL-6 and TNF-α increased with the progression of HDP (P<0.05). The AUC of serum TC, TG, HDL-C and LDL-C levels for predicting HDP were 0.759, 0.854, 0.770 and 0.785, respectively. The AUC of serum Lp-PLA2, CRP, IL-6 and TNF-α levels for predicting HDP were 0.873, 0.991, 0.966 and 0.999, respectively. Conclusion: The levels of blood lipid and serum inflammatory factor are closely related to HDP, which has certain value in predicting the occurrence and development of HDP.